Interferon-Induced Transmembrane Protein 1 Restricts Replication of Viruses That Enter Cells via the Plasma Membrane - Smith, S. E. (J Virol, 2019)
The acute antiviral response is mediated by a family of interferon-stimulated genes (ISGs), providing cell-intrinsic immunity. Mutations in genes encoding these proteins are often associated with increased susceptibility to viral infections. One family of ISGs with antiviral function is the interferon-inducible transmembrane proteins (IFITMs), of which IFITM3 has been studied extensively. In contrast, IFITM1 has not been studied in detail. Since IFITM1 can localize to the plasma membrane, we investigated its function with a range of enveloped viruses thought to infect cells by fusion with the plasma membrane. Overexpression of IFITM1 prevented infection by a number of Paramyxoviridae and Pneumoviridae, including respiratory syncytial virus (RSV), mumps virus, and human metapneumovirus (HMPV). IFITM1 also restricted infection with an enveloped DNA virus that can enter via the plasma membrane, herpes simplex virus 1 (HSV-1). To test the importance of plasma membrane localization for IFITM1 function, we identified blocks of amino acids in the conserved intracellular loop (CIL) domain that altered the subcellular localization of the protein and reduced antiviral activity. By screening reported data sets, 12 rare nonsynonymous single nucleotide polymorphisms (SNPs) were identified in human IFITM1, some of which are in the CIL domain. Using an Ifitm1(−/−) mouse, we show that RSV infection was more severe, thereby extending the range of viruses restricted in vivo by IFITM proteins and suggesting overall that IFITM1 is broadly antiviral and that this antiviral function is associated with cell surface localization. IMPORTANCE Host susceptibility to viral infection is multifactorial, but early control of viruses not previously encountered is predominantly mediated by the interferon-stimulated gene (ISG) family. There are upwards of 300 of these genes, the majority of which do not have a clearly defined function or mechanism of action. The cellular location of these proteins may have an important effect on their function. One ISG located at the plasma membrane is interferon-inducible transmembrane protein 1 (IFITM1). Here we demonstrate that IFITM1 can inhibit infection with a range of viruses that enter via the plasma membrane. Mutant IFITM1 proteins that were unable to localize to the plasma membrane did not restrict viral infection. We also observed for the first time that IFITM1 plays a role in vivo, and Ifitm1(−/−) mice were more susceptible to viral lung infection. These data contribute to our understanding of how ISGs prevent viral infections.